The association between age and acute pain sensitivity in patients with Herpes Zoster - Liu Wang; Aiguo Li; Zhixuan Lan; Shengrong Xu; Ruilin He; Zongbin Jiang (Scientific Reports)
Abstract Herpes zoster has a well-established increased incidence in older adults, but the relationship between age and acute pain severity remains less clear. This retrospective study aimed to explore the association between age and pain intensity in Herpes zoster patients. A total of 613 patients treated at the Second Affiliated Hospital of Guangxi Medical University were included. Pain intensity was measured using the Numerical Rating Scale-11, and statistical models were applied to evaluate age-related pain differences while controlling for confounders. While older age was associated with higher pain scores (β = 0.02, p < 0.001), the effect size was small. Other factors, such as pain duration and inflammatory markers (e.g., CRP levels), showed stronger associations with pain severity. These findings suggest that age may not be the dominant factor in Herpes zoster pain severity, and a more comprehensive approach is required for risk assessment and pain management in clinical practice.